Double Medical Image Cryptosystem Based on Quantum Walk - Bassem Abd-El-Atty; Mohammed A. El-Affendi; Samia Allaoua Chelloug; Ahmed A. Abd El-Latif (IEEE Access, 2023)
With the growing capability of realizing quantum computers, most medical image cryptosystems may crash. This work proposes a novel double medical-image encryption algorithm using quantum walks and logistic mapping. In the proposed encryption technique, the double plain images are split into two different images, one of which has the high 4 bits of each image and the other has the low 4 bits. The high-bit image is encrypted using quantum walks because it possesses a large portion of information, and the other image, which possesses a small portion of information, is encrypted using the logistic map. The moderate values of information entropy, NPCR, UACI, and PSNR for the tested images are 7.9993, 99.6143%, 33.4659%, and 7.4819, respectively. The experimental results prove the efficiency of the proposed double medical image encryption technique.